Climate change in the Asian highlands: socio-economic implications for the Mekong Region - Xu, Jianchu (Earthscan, 2011)
This chapter looks at the implications of climate change in the Asian highlands and growing socio-economic pressures on resources that, in combination, are set to pose far-reaching impacts for the diverse ecosystems and societies in the Mekong region. This chapter argues for more inclusive goernance processes to adress these complex and multi-layered impacts, both climate- and development-related, within the various socio-political and ecological landscapes in the Mekong region.